Current debates in the social sciences - David, Randolf S. (Quezon City U.P. Diliman Interactive Learning Center, 2005)
The third in a series of four lectures under the project Exploring the Technology of Videoconferencing in Teaching Social Science II.
Lecture delivered on February 28, 2005.
Executive producer, Amelia Guevara ; Associate producer, Celia Adriano ; Director, Grace Javier-Alfonso ; Co-produced by, U.P. Computer Center, U.P. Open University Media Center, Department of Electrical and Electronics Engineering, College of Engineering.
Series lecturer: Randolf S. David ; Moderator: Malaya C. Ronas.
Keywords: Social sciences -- Philosophy -- Congresses; Modernism (Christian theology) -- Congresses; Postmodernism -- Congresses; Sociology -- Philosophy -- Congresses